Pelatihan Pembuatan Roti Pizza Melalui Pembelajaran Sentra Memasak Anak Usia 4-6 Tahun di PAUD Terpadu Al-Banna Mataram - Ehyani, Zuldi; Henny, Henny; Sunipa, Sunipa; Risia, Aulia Febrina; Prana, Satrio Adi; Tina, Tina; Pratama, Anggaditya (Abdi Masyarakat, 2022)
The aim of training in making pizza rot through cooking centers is so that children can learn about size, texture, and taste. They can learn different types of food and can compare foods, recognize, similarities and differences. children can also develop confidence when they have the opportunity to prepare food that will be enjoyed by classmates and teachers, with only planning and thinking, cooking activities can be an important part of the curriculumchild learning. the selection of training in Islamic Pearl PAUD because the PAUD already uses the learning center model but there is no cooking center learning, the PAUD only uses a few centers. The method used in community service activities is in the form of counseling / education using the demonstration method. Children involved are 20. Community service activities include training in making pizza bread in order to develop all aspects of development, growth, various kinds of intelligence, creativity, imagination, independence and racial self-confidence of children.